Pengaruh Lingkungan Keluarga Terhadap Akhlak Siswa Sebagai Pembentuk pola kepribadian - Afivah Laela Sari; Sri Mulyani (AL GHAZALI: Jurnal Pendidikan dan Pemikiran Islam, 2024)
The family as the first educational environment is very influential in shaping children's personality patterns. It is in the family that children are first introduced to values ​​and norms. Family education provides the basic knowledge and skills, religion and beliefs, moral values, social norms and outlook on life that children need. This research aims to determine the influence of the family environment on the morals of class IX students at MTs Negeri 1 Cilacap. This research uses quantitative research with data collection techniques namely observation, interviews, questionnaires and documentation. The subjects in this research were class IX students of MTs Negeri 1 Cilacap. Meanwhile, the object of this research is the influence of the family environment on the morals of class IX students at MTs Negeri 1 Cilacap. The type of research carried out is field research with a quantitative approach.  The results of this research show that there is an influence of the family environment on the morals of class IX students at MTs Negeri 1 Cilacap. The results of the Pearson correlation r = 0.49 which can be categorized as MEDIUM based on the coefficient interpretation table. For the value of the determination coefficient, the value obtained is r = 0.49.  KP = 〖0.49〗^2= 0.2401 then, KP X 100% = 0.2401× 100% = 24.01%. So, this figure shows that the contribution (contribution) of the influence of the family environment on student morals is 24.01%. In the sense that the other 75.99% is influenced by other variables that were not observed in this study